PENGARUH PENGEMBANGAN KARIR, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V PEKANBARU - Lamita Asry Silaban; Raden Lestari Garnasih; Mida Aprilina Tarigan (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
This study aims to determine the effect of career development, work motivation and work discipline on employee performance at PT. Perkebunan Nusantara V Pekanbaru , as many as 218 people. The sampling technique in this study used proportionate stratified random sampling namely 141 head office employees. Sources of data used are primary data collected by distributing questionnaires as research instruments, and the analysis tool is multiple linear regression analysis through the SPSS For Windows 26 program. With employee performance as the dependent variable and three independent variables, namely career development, work motivation, and work discipline. The results of this study indicate that: 1)Career development has a significant effect on employee performance,2)Work motivation has a significant effect on employee performance, and 3)Work discipline has a significant effect on employee performance.